2018
DOI: 10.31276/vjste.60(1).38
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children with idiopathic nephrotic syndrome according to clinical types

Abstract: Idiopathic nephrotic syndrome (INS) is a major manifestation of chronic idiopathic glomerulonephritis and a common disease in children. The cause and pathogenesis of the disease have not been clarified so far. The treatment is usually a long-term process, from a few months to several years, even decades, including the period of hospitalisation, outpatient treatment period and follow-up period after treatment. The INS patients are negatively affected by the disease and its treatment process. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…These findings were similar to previous reports that also found that the general QoL of children with NS substantially declined compared to that of healthy children. 18,21 The same findings were observed in a study conducted at Soba Teaching Hospital, Sudan, which showed that all scores were significantly lowered in Sudanese children with NS. 19 This study found that the HRQoL of children with NS was not affected by their age group, except there was significant impairment in school performance in older children.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These findings were similar to previous reports that also found that the general QoL of children with NS substantially declined compared to that of healthy children. 18,21 The same findings were observed in a study conducted at Soba Teaching Hospital, Sudan, which showed that all scores were significantly lowered in Sudanese children with NS. 19 This study found that the HRQoL of children with NS was not affected by their age group, except there was significant impairment in school performance in older children.…”
Section: Discussionsupporting
confidence: 77%
“…These findings were similar to previous reports that also found that the general QoL of children with NS substantially declined compared to that of healthy children. 18 , 21 The same findings were observed in a study conducted at Soba Teaching Hospital, Sudan, which showed that all scores were significantly lowered in Sudanese children with NS. 19 …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The HRQoL of children with ITP and their parents were remarkably lower in comparison with the healthy children. 26,27 In Vietnam, research on HRQoL have been paid attention recently, 28,29 however, HRQoL for chronic ITP patients is still lack of in the country. This study aims to evaluate the HRQoL among Vietnamese children with chronic ITP.…”
Section: Introductionmentioning
confidence: 99%